Ultrastructural findings in semen samples of infertile men infected with Chlamydia trachomatis and mycoplasmas - Gallegos Ávila, Guadalupe; Ortega Martínez, Marta Graciela; Ramos González, Benito; Tijerina Menchaca, Rolando; Ancer Rodríguez, Jesús; Jaramillo Rangel, Gilberto (American Fertility Society, 2009)
The aimofthis study was to describe the ultrastructural features observed in semen samples of men with infertility and subfertility of unknown cause infected with Chlamydia trachomatis and mycoplasmas. The findings observed byultrastructure included destruction or persistence of bacteria in leukocytes, phagocytosis of spermatozoa by leukocytes, and structural damage of spermatozoa. (Fertil Steril 2009;91:915–9. 2009 by American Society for Reproductive Medicine.)